IMPACT OF ORTHODONTIC DYSFUNCTIONS ON THE DEVELOPMENT OF JOINT OSTEOARTHRITIS - Oleg Solomon; Norina Consuela Forna; Doriana Agop Forna; Irina Adriana Beuran; Diana Cornea; Kamel Earar (Romanian Journal of Oral Rehabilitation)
Orthodontic dysfunctions, including malocclusion, open occlusion and retrognathism, can contribute to the development of articular osteoarthritis by increasing mechanical stress on the temporomandibular joint (TMJ). Osteoarthritis is a chronic degenerative condition that affects the articular cartilage, leading to pain, dysfunction and decreased quality of life. This article investigates the mechanisms by which orthodontic dysfunctions can accelerate TMJ degeneration, emphasizing the influence of biomechanical and pathophysiological factors. Understanding the connection between dental malpositions and osteoarthritis is essential for establishing effective methods of prevention and treatment, having the potential to reduce the incidence and severity of osteoarthritis among patients with orthodontic dysfunctions. The proposed multidisciplinary approach aims at collaboration between orthodontics and rheumatology to ensure proactive clinical intervention, thus contributing to the long-term health of patients.